4D synchrotron X-ray tomographic study of the influence of transverse magnetic field on iron intermetallic compounds precipitation behavior during solidification of Al–Si–Fe alloy. (April 2022) - Cao, Jiawei; Shuai, Sansan; Huang, Chenglin; Hu, Tao; Chen, Chaoyue; Wang, Jiang; Ren, Zhongming
Abstract: Hard and brittle iron intermetallic compounds (IMCs) will be formed during solidification due to the existence of iron element in Aluminum alloy. These IMCs will cause cracks or fractures in the material, which can deteriorate the mechanical properties. Synchrotron X-ray tomography were used to study the real time formation and growth dynamics of IMCs in Al-10 wt.%Si-1 wt.%Fe alloy during solidification under transverse magnetic field (TMF). The results indicated that the precipitation behavior of IMCs was significantly affected by 0.07 T TMF. The IMCs were observed to form only on the periphery of the sample under TMF, comparing with random distribution without TMF. In addition, the growth dynamics of IMCs were also affected by TMF. When solidified without TMF, an explosive nucleation and growth of IMCs was presented at the intermediate solidification stage, where a large number of fine IMCs precipitated at the entire regions of the sample. In contrast, the IMCs located at the periphery areas were observed to grow steadily under TMF. The growth rate and formation mechanism of IMCs were also quantified and revealed, showing difference with and without TMF. The tip growth rate was relatively stable when solidified with TMF, while an accelerating growth stage was presented when TMF is absent. The discrepancy in precipitation behavior of IMCs could be best explained as the convection of the melt resulted from the applied TMF. The TMF was demonstrated to generate a directional flow with a velocity of ∼3.3 mm/s. The flow was supposed to drive the Fe solute from the center to the edge of the sample, providing enough Fe solute for IMCs to nucleate and grow on the surface of the sample. In addition, due to the influence of TMF induced flow on the distribution of Fe solute and temperature, the morphology and tip growth rate of IMCs were also affected. The result presented in current study provides the possibility to regulate the precipitation behavior of Fe-rich IMCs in Al alloys. The imposed TMF also shows the potential application in Fe removal by driving the Fe solute to the surface of sample in Al alloys. Highlights: Growth dynamic of Fe-intermetallic was studied in-situ by X-ray under magnetic field. Magnetic field affect the precipitation amount and behavior of Fe-intermetallic. The Fe solute directionally flow toward the edge of sample under magnetic field. Fe-intermetallics prefer to nucleate on the oxide layer under magnetic field. Magnetic field can be used to remove Fe-intermetallic from aluminum alloys.